B7-H1/PD-1 Blockade Therapy in Urological Malignancies: Current Status and Future Prospects. Issue 5 (September 2015) - Yu, Lun; Wang, Yonghua; Shao, Shixiu; Yang, Meng; Niu, Haitao; Yu, Qinchao; Wang, Xinshen
The stimulatory and inhibitory coreceptors expressed by T lymphocytes are known to play critical roles in regulating cancer immunity. An array of inhibitory coreceptors involved in the inhibition of T-cell functions and the blockade of immune activation have been discovered in recent years, the most important of which are cytotoxic T-lymphocyte antigen-4 (CTLA-4), programmmed death-1 (PD-1), and B7 homolog 1 (B7-H1). Immunotherapies targeting T-cell coinhibitory molecules have proved to be effective in cancer treatment. Several kinds of monoclonal antibodies have been tested in preclinical studies, with better outcomes than conventional therapies in many malignancies. Common urological malignancies including renal cell carcinoma, bladder cancer and prostate cancer are supposed to be immunogenic cancer types and not so sensitive to conventional therapies as other malignancies. This review will focus on B7-H1/PD-1 blockade therapy in urological malignancies, summarizing the results of clinical trials as well as the challenges and prospects of this emerging immunotherapy.